2002
DOI: 10.1136/gut.50.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin is an important determinant of renal function in a rat model of acute liver and renal failure

Abstract: Background and aims: Renal failure occurs in approximately 55% of patients with acute liver failure. We have previously shown that plasma endothelin 1 concentrations are elevated in patients with acute liver failure and the hepatorenal syndrome. There are few reported satisfactory animal models of liver failure together with functional renal failure. In this study, a rat model of acute liver failure induced by galactosamine that also develops renal failure was first characterised. This model was used to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 39 publications
6
56
0
5
Order By: Relevance
“…ET-1 showed a significant elevation in the MHRS model in the present study, which supports the previous proposal of being a biomarker of HRS (Anand et al, 2002) due to the increased endothelin (A) of the renal cortex which is important in the pathogenesis of renal failure that occurs in patients with acute liver failure or HRS. Urinary NAG was significantly elevated in the MHRS model in the present study reflecting tubular dysfunction and kidney parenchymal damage as reported by Skálová (2005).…”
Section: Discussionsupporting
confidence: 79%
“…ET-1 showed a significant elevation in the MHRS model in the present study, which supports the previous proposal of being a biomarker of HRS (Anand et al, 2002) due to the increased endothelin (A) of the renal cortex which is important in the pathogenesis of renal failure that occurs in patients with acute liver failure or HRS. Urinary NAG was significantly elevated in the MHRS model in the present study reflecting tubular dysfunction and kidney parenchymal damage as reported by Skálová (2005).…”
Section: Discussionsupporting
confidence: 79%
“…It has also been determined that a patient with a liver disease had a decline in renal blood flow that indicated renal vasoconstriction (Guarner et al 1987). Anand et al (2002) also showed that treatment of DGalN results in renal failure that manifests itself through the decrease in the renal blood flow, creatinine clearance, along with a rise in plasma endothelin-1 (ET-1) concentration, and also upregulation of ET-1 receptors in renal cortex. Catal and Bolkent (2008) reported that animals administered 500 mg/kg D-GalN had distinct degenerative changes, particularly in the proximal tubular cells and glomerulus when compared to the kidney tissues of control groups.…”
Section: Discussionmentioning
confidence: 99%
“…GalN-induced liver injury has also been linked to renal failure (Javle et al 1998). Anand et al (2002) showed that treatment of D-GalN results in renal failure manifested by the decrease in renal blood flow, creatinine clearance in renal cortex. It was also reported that a patient suffering from liver disease showed a decrease in the renal blood flow, indicating renal vasoconstriction (Guarner et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Classically, HRS is associated with the end-stage liver cirrhosis and it has been observed that renal failure occurs with this liver disease in about 50% of patients. Anand et al (2002) reported that d-GalN intoxication causes liver injury followed by renal impairment which is manifested by the decrease in renal blood flow and creatinine clearance. Renal dysfunction due to d-GalN administration was also manifested by the increase in serum urea and creatinine levels and kidney TBARS and MPO activity together with degenerative changes in kidney histology (Tunc et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Progressive impairment of liver cells due to oxidative stress would lead to life threatening complications if left untreated (Wolf, 1999). Anand et al (2002) reported d-galactosamine-induced acute liver failure results in renal damage and is mediated by endothelin receptors. Recently, the term hepatorenal syndrome (HRS) has been introduced to define the development of renal failure related with hepatocellular dysfunction (Epstein, 1996).…”
Section: Introductionmentioning
confidence: 99%